DIGITAL ARTS AND ECO-CONSCIOUSNESS: INTERPRETING ENVIRONMENTAL AND TECHNOLOGICAL POLICIES THROUGH VISUAL CULTURE IN INDIA - Mishra, Satish Kumar; Sudhashil, Shubham; Alexander, Dr. Daisy; Chaudhery, Sanjay; Upreti, Anupam; Rai, Kshitij Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The interplay between technology and the environment presents a defining challenge of our era, as rapid technological progress brings both advancements in human life and considerable threats to nature. Amidst pressing environmental challenges, the urgency to harness technology for positive transformation while respecting ecological values becomes paramount to secure a sustainable future for generations to come. Therefore, this paper proposes a comprehensive roadmap for harmonizing technology and the environment, promoting a holistic and synergistic approach. The paper explores the intricate relationship between technology and the environment, delving into the potential for these seemingly disparate forces to align towards sustainability. Technological advancements have led to remarkable improvements in communication, transportation, healthcare, and energy efficiency. However, this progress has also engendered escalating environmental issues such as climate change, pollution, and resource depletion. Consequently, striking a delicate balance between technological development and environmental conservation becomes crucial for society's sustainable future. The paper examines the promising potential of technology as a solution to environmental challenges, emphasizing green technologies, renewable energy sources, and innovative waste management and conservation practices. Moreover, it critically assesses the potential risks and unintended consequences of certain technological endeavours, underscoring the significance of ethical considerations and precautionary measures. The role of various stakeholders, including governments, businesses, and individuals, is highlighted as they jointly shape the interface between technology and the environment, seeking collaborative and proactive solutions.